EVALUASI ADVERSE DRUG REACTIONS DAN EFEKTIVITAS PENGGUNAAN KETOROLAK PADA PASIEN PASCA BEDAH SARAF DI RUMAH SAKIT UMUM PENDIDIKAN DR. WAHIDIN SUDIROHUSODO MAKASSAR - Hendra Herman; Zullies Ikawati; Rina Handayani (As-Syifaa Jurnal Farmasi, 2013)
Pain is often experienced by patients treated in the hospital and is the most frequently reported events in post-surgical patients. Ketorolac associated with the incidence of adverse reactions include, the incidence of acute renal failure and bleeding disorders. The purpose of the study was to observe and report on the profile of adverse reactions include the use of ketorolac on renal function and hemostasis as well as the effectiveness of the analgesic ketorolac. A total of 20 patients who received ketorolac compared to the value of the glomerular filtration rate (GFR), bleeding time (BT), Blood Clotting Time (CT), prothrombin time (PT) and International Normalized Ratio (INR) between before and after patients received ketorolac. Compared to the value of the Visual Analog Scale (VAS) ranging V day I to day administration of ketorolac. One of 20 patients (5%) who use ketorolac for 5 days had decreased GFR by 66.70%.. Whereas for hemostasis testing showed that ketorolac can influence hemostatic seen from increasing on BT  (0,04; p <0,05), CT (0,02; p <0,05), PT value (0,03, p <0,05), as well as an increase in INR value (0,03; p <0:05) but still in normal range. Comparison of the mean VAS score from day one to day five showed that administration of ketorolac can reduce pain and disappeared on day 4, where VAS values between days 4 and 5 showed no statistical difference (0,56; p> 0,05). Conclusion. incidence of renal damage incident occurred at 5%, and may affect hemostatic function in patients. Resolution of pain may occur at day 4 ketorolac administration.Key word : Evaluation, Adverse Effects, Effectiveness, Ketorolac, Post-Nerve Surgical Patient